Pendekatan Kualitatif dalam Akuntansi Syariah: Konsep, Metodologi, dan Implikasinya - Febrita; Heni Saputri; Peny Cahaya Azwari (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
This study examines the role of qualitative approaches within the context of Islamic accounting, with a focus on exploring the social, ethical, and spiritual dimensions inherent in value-based financial practices. In this context, qualitative methodology provides a more nuanced understanding compared to quantitative approaches, which tend to be limited to numerical data. This research employs a literature review method to identify concepts, methodologies, and implications of qualitative research in Islamic accounting. The findings indicate that qualitative approaches, through strategies such as phenomenology, case studies, and ethnography, offer a holistic depiction of practices and values within Islamic accounting. Moreover, the results suggest practical implications for the development of Islamic Social Reporting (ISR) and highlight the need for regulations that are more adaptable to the social realities of the Muslim community. Therefore, qualitative approaches not only contribute to the richness of academic research but also facilitate a more responsive and humanistic practice in accounting.